Design of Highly Stretchable, Self‐Adhesive Ionic Conductive Hydrogels for Wearable Strain Sensors - Huawei Gao; Yupan Han; Mengjie Huang; Jianwei Li; Hongling Sun; Guojie Li; Lin Dong; Xianhu Liu; Chuntai Liu; Changyu Shen (Advanced Sensor Research)
Abstract Conductive hydrogels (CHs) have received numerous attentions for potential applications in flexible electronics. However, the construction of high‐performance CHs with high stretchability, favorable electrical conductivity, and reversible adhesiveness simultaneously still remains a great challenge. Herein, an ionic CH with the above characteristics is proposed via introducing phytic acid (PA) into semi‐interpenetrating cross‐linked network of poly(acrylamide‐co‐N‐(hydroxymethyl) acrylamide) and chitosan hydrogels. The synergy of hydrogen bonds and electrostatic interactions endows the obtained hydrogel with high stretchability (1131%), toughness (88.32 kJ·m−3), and satisfactory adhesiveness (25.78 kPa to wood). The presence of PA enables the composite hydrogel to exhibit favorable electrical conductivity. Impressively, the resultant hydrogel can be assembled into the wearable strain sensor to present high sensitivity of 1.32 in the wide strain response range (0–1131%), rapid response time (340 ms), and excellent cyclic stability. More importantly, the prepared stain sensor can precisely recognize complicated human movements and physiological activities and realize the information encryption, making this hydrogel a promising candidate for preparing high‐performance electronics.